Energy consumption and economic growth in the E7: A comprehensive analysis using random effect and PMG models - Oktavilia; Damayanti Nadia; Arfinto Erman Denny; Wahyuningrum Indah Fajarini Sri (E3S Web of Conferences)
This study investigates the relationship between economic growth, agricultural practices, greenhouse gas emissions, and energy consumption in the E7 countries—Brazil, China, Indonesia, India, Mexico, Russia, and Turkey—using Random Effect and Pooled Mean Group (PMG) models. By analyzing panel data from 1992 to 2020, the research explores both short- and long-term impacts of GDP, agricultural land use (AGRI), greenhouse gas emissions (TGHG), and rice production (RICE) on energy consumption. The findings reveal that in the long run, GDP, AGRI, and TGHG have significant positive effects on energy consumption, indicating that economic growth, agricultural expansion, and environmental impact are key drivers of energy demand. However, RICE shows no significant long-term influence. In the short run, only TGHG remains a significant factor, while GDP and AGRI do not show immediate effects on energy consumption. These results underscore the importance of sustainable policies that address the long-term drivers of energy consumption, particularly in rapidly growing economies like the E7. The study contributes to the literature by providing insights into the unique dynamics of emerging economies, emphasizing the need for balanced strategies that promote economic growth while ensuring environmental sustainability